Risk of New-Onset Atrial Fibrillation Post-cavotricuspid Isthmus Ablation in Typical Atrial Flutter Without History of Atrial Fibrillation - Li, Jia-hui; Xie, Hai-yang; Chen, Yan-qiao; Cao, Zhong-jing; Tang, Qing-hui; Guo, Xiao-gang; Sun, Qi; Ma, Jian (Frontiers in Physiology, 2021)
Aims: To describe the incidence of atrial fibrillation (AF) after cavotricuspid isthmus (CTI) ablation in typical atrial flutter (AFL) patients without history of AF and to identify risk factors for new-onset AF after the procedure. Methods: A total of 191 patients with typical AFL undergoing successful CTI ablation were enrolled. Patients who had history of AF, structural heart disease, cardiac surgery or ablation, or received anti-arrhythmia drug after procedure were excluded. Clinical and electrophysiologic data were collected. Results: There were 47 patients (24.6%) developing new AF during a follow-up of 3.3 ± 1.9 years after CTI ablation. ROC curves indicated that the cut-off values of left atrial diameter (LAD) and CHA2DS2-VASc score were 42mm and 2, with area under curve of 0.781 and 0.550, respectively. Multivariable Cox regression analysis revealed that obstructive sleep apnea (hazard ratio (HR) 3.734, 95% confidence interval (CI) 1.470-9.484, P=0.006), advanced interatrial block (aIAB) (HR 2.034, 95%CI 1.017-4.067, P=0.045), LAD >42mm (HR 2.270, 95%CI 1.478-4.969, P=0.001) and CHA2DS2-VASc score >2 (HR 2.123, 95%CI 1.118-4.034, P=0.021) were independent risk factors of new-onset AF. Conclusions: A combination of OSA, aIAB, LAD >42mm and CHA2DS2-VASc >2 was a strongly high risk for new-onset AF after ablation for typical AFL, and it had significance in post-ablation management in clinical practice.